Mapping geologic features onto subducted slabs - Harmon,N; Rychert,C; Collier,J; Henstock,T; van,Hunen J; Wilkinson,JJ (Geophysical Journal International, 2019)
Estimating the location of geologic and tectonic features on a subducting plate is important for interpreting their spatial relationships with other observables including seismicity, seismic velocity and attenuation anomalies, and the location of ore deposits and arc volcanism in the over-riding plate. Here we present two methods for estimating the location of predictable features such as seamounts, ridges and fracture zones on the slab. One uses kinematic reconstructions of plate motions, and the other uses multidimensional scaling to flatten the slab onto the surface of the Earth. We demonstrate the methods using synthetic examples and also using the test case of fracture zones entering the Lesser Antilles subduction zone. The two methods produce results that are in good agreement with each other in both the synthetic and real examples. In the Lesser Antilles, the subducted fracture zones trend northwards of the surface projections. The two methods begin to diverge in regions where the multidimensional scaling method has its greatest likely error. Wider application of these methods may help to establish spatial correlations globally.